Women's health in primary care: an experience report on gestational syphilis and adolescent pregnancy (Research, Society and Development, 2023)
Objective: To report the experience of medical students at the ESF Parque Verde Unit in terms of interaction, teaching, service, community and management at the Centro Universitário Metropolitano da Amazônia. Method: This is an experience report, about experiences selected by students of two users of the Unified Health System (SUS), addressing the theme of teenage pregnancy and gestational syphilis, it was developed in a Family Health Strategy (ESF) located in the Parque Verde neighborhood, in the city of Belém - PA, from August to December 2022. Results: During our experience in primary care, we implemented strategies to strengthen the early diagnosis and adequate treatment of syphilis in pregnant women. With regard to teenage pregnancy, the comprehensive approach must consider the biopsychosocial aspects of adolescents. It is essential to offer emotional support, adequate information on sexual and reproductive health, and access to qualified health services. Conclusion: Addressing gestational syphilis and teenage pregnancy in primary care is essential to promote women's health and well-being. Our experience has shown that early detection and adequate treatment of gestational syphilis are effective in preventing vertical transmission of the disease. In addition, the sensitive and comprehensive approach to teenage pregnancy contributes to access to prenatal care and family planning actions among pregnant adolescents. These interventions are critical to improving health outcomes and ensuring a healthy future for women.